Victims of War in the Former Yugoslavia
Professor Bassiouni gives introduction. Excerpts from various tapes, showing exellent overview of conflict, including interviews with survivors and witnesses of masacres, camps, excavation of mass grave sites, refugees, Arkan and his troops in action.